Atypical naevus, dysplastic naevus, dyspastic naevus syndrome – nomenclature controversy, diagnostic difficulties and prognostic perspectives - Góralska, Agnieszka; Błaszczyk, Jan (Dermatology Review/Przegląd Dermatologiczny, 2013)
The problem of melanocytic naevi concerns most dermatological patients. There are different classifications regarding clinical aspects, localization and the histopathological picture of naevi and names of researchers who described the lesions. Atypical naevus, dysplastic naevus and atypical naevus syndrome (B-K mole syndrome, familial atypical multiple mole melanoma [FAMMM] syndrome, dysplastic naevus syndrome) are an important clinical, therapeutic and descriptive problem. For 30 years the diagnostic criteria of atypical naevus, dysplastic naevus and atypical naevus syndrome have been a source of confusion. Atypical naevi are defined by clinical presentation and histopathological diagnosis describes dysplastic naevi. Whether these lesions represent a precursor of melanoma remains controversial, because histopathological dysplasia in melanocytic lesions can be a reversible process. A number of factors, such as genetic predisposition, illnesses and UV radiation, influence the frequency of dysplastic naevus appearance. Dermoscopy is a gold standard in the diagnosis of melanocytic naevi.